الدور التربوي للمؤسسات العقابية و علاقته بإعادة تأهيل المساجين - بـورنــي, نسيـم (Sciences humaines, 2014)
أقيمت السجون قديما بغرض الانتقام من المجرمين نظرا للجرم الذي اقترفوه، فكان الهدف من العقوبة هو الانتقام فحسب دون مراعاة الظروف الموضوعية التي تؤدي بالأفراد إلى اقتراف الجريمة ، إلا أنه بفضل فلاسفة التنوير و بعض الديانات كالدين الإسلامي و الديانة المسيحية ، تغيرت النظرة إلى المسجون حيث يعتبر إنسانا أخطأ و يمكن توبته وذلك  بأخذ بعين الاعتبار الأسباب  الموضوعية التي  دفعته  إلى  اقتراف  الجريمة  ، كالفقر  و  البطالة و الجهل و غير ذلك من الأسباب ، و من هنا برزت نظرة جديدة تحاول استئصال هذه الأسباب التي تؤدي بالأفراد إلى اقتراف الجريمة ، و ذلك من خلال الاستفادة من فترة السجن في تمكين العاطلين من اكتساب  مهنة و تمكين الجاهلين و الأميين من التعلم و ذلك لاكتساب أفكار جديدة و مستنيرة تغير سلوكهم ، و من هذا المنطلق أصبح للمؤسسات العقابية دور تربوي في إعادة تأهيل المساجين من جميع جوانب  شخصيتهم  العقلية و النفسية و الاجتماعية و المهنية ، و قد أثمر تطور الأفكار العقابية بهذا الشأن تقرير الحد الأدنى لمعاملة المساجين و ذلك في جنيف سنة 1945 ، و التي تحاول تطبيقه الجزائر بعد أن تبنته و أصبح من انشغالات السياسة العقابية في الجزائر    Prisons were created out of vengeance criminals because of the crimes they have committed. So the aim of the sanction was only vengeance without taking into consideration the objective factors which lead the individuals to commit crimes. Thanks to philosophers and religions as the religion of Islam and the Christian one. That changed the view about prisoners. The prisoner, then , is considered as an individual who committed an error and can convert , or to take into account the objective reasons which lead him to commit the crime , such as poverty , unemployment , illiteracy and so on ….  . And thus appeared a new that tries to extract the factors of the crime. Prisoners can take profit during the period of their prison; the unemployed can inquire new jobs, illiterates can learn and inquire new positive ideas which help them to change their behaviors. Since then, the punishment establishments have an educational role in the personality; mental, psychological, social and professional.  The evolution of the penitentiary ideas permitted, minimum treatment of the prisoners in Geneva in 1954.  Algeria tries to apply these rights. The penitentiaries